Analisis Hukum Terhadap Wanprestasi dalam Proyek Konstruksi yang Melibatkan Pihak Perorangan: Studi Kasus Pembangunan Guesthouse. - Prasetyo, Didik; Putranto, Rahmat Dwi; Harvelian, Agnes (Neolectura, 2024)
In the realm of construction, contracts form the fundamental basis of projects involving multiple parties with clear responsibilities and obligations. This research explores a case of breach of contract (wanprestasi) in a construction project involving an individual, which not only caused financial and reputational harm to other parties involved but also compromised the integrity and quality of the project. The legal framework governing construction services and contracts, including Article 1 paragraph (3) of Law Number 2 of 2017 concerning Construction Services, sets the ground for understanding obligations and rights under Indonesian civil law. The methodology employed in this study is a qualitative analysis, focusing on the application of legal principles, relevant regulations, and real-life practices related to cases of breach of contract using literature reviews and case document analysis. This approach has allowed for an in-depth understanding of the legal norms and the actual enforcement of laws in similar situations. The findings reveal that the specific breaches included not meeting agreed specifications and delays in project completion, which are deemed as wanprestasi under Article 1243 of the Indonesian Civil Code. These violations stem from poor project management, opaque fund usage, and unilateral decisions by the executing party, highlighting the need for stringent legal enforcement and protection for the aggrieved parties. Keywords: Construction Law, Breach of Contract, Legal Enforcement, Project Management, Civil Law